Developing a patient-educator program for adolescents with juvenile arthritis: Exploring motivation sources, barriers, and facilitators - Morin, Marie-Paule; Shah, Aimun Qadeer; Mylopoulos, Maria; Pomey, Marie-Pascale; Bowen, François; Grierson, Lawrence; Bourque, Claude Julie (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2026)
Background: Patients can be valuable contributors to medical education, offering nuanced perspective and guidance, based on lived experience. While numerous training programs have integrated adult patients in this manner, very few have engaged adolescent patients. Recognizing adolescent educators may be particularly helpful in teaching pediatric conditions, this study appraises the potential for including those with juvenile arthritis in pediatric rheumatology training.Methods: Using an exploratory qualitative approach, we conducted semi-structured interviews with adolescents with juvenile arthritis receiving treatment at two tertiary-care pediatric centres in Canada about the motivations, perceptions, facilitators, and barriers that influence their engagement as patient educators. The interview transcripts were analyzed using an iterative qualitative descriptive method.Results: Participants (n = 19, aged 13-18) identified intrinsic factors, such as learning about their condition and socializing with peers, and extrinsic factors, such as helping students learn and promoting greater disease awareness, as relevant drivers for participating as patient educators. They pointed to balancing school and medical appointments, transportation, and discomfort with sharing personal experiences in large groups as barriers. Parental support, accruing volunteer hours, and engaging health professionals in the teaching sessions were seen as facilitators that could meaningfully enhance the relevance and impact of adolescents’ contributions to medical education.Conclusion: Adolescents with juvenile arthritis are motivated to participate as patient educators. Understanding the factors that promote their involvement supports the development of training initiatives involving adolescents that are likely to be successful and sustainable.